Pengolahan Ikan Teri Kering Menjadi Abon Asin Gammi - Andi Muhamad Iqbal Akbar Asfar; Akhmad Rifai; M. Ilham Nurdin; Jeanne Dewi Damayanti; A.M.Irfan Taufan Asfar (Universitas Lancang Kuning, 2021)
IbM (Science and Technology for the Community) is part of community service in empowering partners. This program is carried out in Cenrana Village, Bone Regency, South Sulawesi Province in processing dried anchovies into Abon Asin Gammi with a population of 2,040 people. During this time, Gammi is a home comestible with a distinctive aroma and very appetizing. However, no one has tried to sell it as a peculiar Bugis product. Therefore, Gammi has the potential to become a peculiar Bugis souvenir in the form of Shredded Salted Gammi. The method of implementation is through three main components of IbM implementation, namely Counseling in the form of short seminar, training and demonstration of Abon Asin Gammi processing and mentoring to partners. The results of Science and Technology for the Community program were able to increase partner knowledge and productivity in processing salted anchovy into Shredded Slated Gammi. The resulting product has two variants are soft and rough which is packaged in pouch packaging with a net weight of 30 grams.